Renal disease in HIV infected patients at University of Benin Teaching Hospital in Nigeria - Okafor, UH (Makerere Medical School, 2011)
BACKGROUND: HIV related renal disease is a common occurrence in patients with HIV infection. It is the third leading cause of end stage renal disease among African-American males between the ages of 20 and 64 years in USA. Renal function impairment has been reported at all stages of HIV infection. The aim of this study is to determine the relationship between severity of renal function impairment and CD4 cell count in HIV infected patients. METHOD: HIV patients presenting at University of Benin Teaching Hospital Benin, City Nigeria from 1(st) January to 30(th) June 2007 were randomly selected and screened for renal functional impairment (RFI). Those with RFI detected by glomerular filtration rate < 60ml/min/1.73m(2) or urine protein creatinine ratio 3 200 were stratified into mild, moderate and severe RFI. Forty patients from each stratum and forty HIV infected patients with normal renal functions were recruited as subjects and control respectively. Their clinical and laboratory parameters were evaluated. The data obtained were analysed using SPSS vs 15.0. RESULTS: Of the HIV patients screened, 53.3% had renal functional impairment. of these, 40.2% had mild, 37.7% had moderate and 22.2% had severe impairment in their renal functions respectively Their mean age was 36.0±8.8 years. The CD4 cell count was found to be 309.75 ± 268.71/ul, 188.45 ± 173.12/ul, and 141.10±126.01/ul among subjects with mild, moderate and severe RFI respectively. The CD4 cell count in control group was 319.05 ± 248.41/ul. The difference was statistically significant. (p = <0.001). CD4 cell count had a significant positive correlation with GFR (r = 0.32, p = 0.042). However, there was a negative correlation between CD4 cell count and proteinuria but this was not statistically significant (r = 0.09, p = 0.173). CONCLUSION: Severity of RFI has a positive correlation with degree of immunosuppression in HIV infected patients.